Outer domains of integrase within retroviral intasomes are dispensible for catalysis of DNA integration. (25th November 2015) - Li, Min; Lin, Shiqiang; Craigie, Robert
Abstract: Retroviral DNA integration is mediated by nucleoprotein complexes (intasomes) comprising a pair of viral DNA ends synapsed by a tetramer of integrase. Current integrase inhibitors act on intasomes rather than free integrase protein. Structural and functional studies of intasomes are essential to understand their mechanism of action and how the virus can escape by mutation. To date, prototype foamy virus (PFV) is the only retrovirus for which high‐resolution structures of intasomes have been determined. In the PFV intasome structure, only the core domains of the outer subunits are ordered; the N‐terminal domain, C‐terminal domain, and N‐terminal extension domain are disordered. Are these "missing domains" required for function or are they dispensable? We have devised a strategy to assemble "hetero‐intasomes" in which the outer domains are not present as a tool to assess the functional role of the missing domains for catalysis of integration. We find that the disordered domains of outer subunits are not required for intasome assembly or catalytic activity as catalytic core domains can substitute for the outer subunits in the case of both PFV and HIV‐1 intasomes.